Era uma vez... significados atribuídos por uma criança com câncer às perdas do adoecimento - Valeriano, Alessandra Rodrigues (2015)
This research had as objective to analyze the meanings attributed by the child to cancer to his or her disease. In the specific case of infant cancer, are highlighted the psychosocial aspects unleashed in the child s experience. The possibility of death and the losses due to the illness, experienced by the child, are, therefore, in the focus of this study. A qualitative research was carried out, as a case study with a four year old and nine months child with leukemia. An investigation method suitable to this age range was utilized with the usage of ludic observation and the Drawing-And-Story Procedure. The losses evinced by the participant are referred as the removal of home, of people sentimentally significant and the restrictions imposed by the treatment. This study highlights the importance of psycho-oncology in the comprehension of infant cancer and its splits in studies regarding family and human development